Effect of eating habits on obesity in adolescents: a study among Chinese college students. Issue 3 (October 2020) - Xie, Qi; Hao, Meng-lei; Meng, Ling-bing; Zuo, Xiao-qin; Guo, Peng; Qiu, Yong; Wang, Qiang; Zhang, Na; Lei, Min
Objective: Obesity has been linked to cardiovascular disease, diabetes, and osteoarthritis. Obesity and overweight pose a serious threat to human health, with an estimated 190 million overweight and obese people worldwide. Thus, we investigated the influence of certain eating habits on weight among Chinese college students. Methods: We conducted a cross-sectional survey of 536 college students in Shijiazhuang, China. The survey included questions about eating habits. We analyzed the relationship between participants' responses and obesity. Results: Sex, residence, speed of eating, number of meals eaten per day, and a diet high in sugar were found to be correlated with obesity. Our results suggest that increasing the number of meals per day, slowing down the pace of eating, and reducing the intake of high-sugar foods have potential benefits for reducing obesity among college students. Conclusions: In the present study, we found that some dietary habits are related to the occurrence of obesity among college-aged individuals.